Potret Kinerja Investasi 6 Tahun Terakhir (2019-2024) Pada DPLK dan Tantangannya - Syarifudin Yunus (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study aims to examine the investment performance of the Financial Institution Pension Fund (DPLK) and the associated challenges, utilizing investment performance data analysis. The findings indicate that the aggregate return on investment for DPLK over the past six years (2019-2024) has reached 6.09%. This is lower than the industry average of 6.99% during the same period. The annual investment performance of DPLK shows the following: 6.18% in 2024, 5.88% in 2023, 3.41% in 2022, 4.06% in 2021, 8.89% in 2020, and 8.17% in 2019. Despite some fluctuations, these results are still considered suboptimal. Key challenges facing DPLK include market volatility, interest rate risk, longevity risk (longer participant lifespan), balancing return and risk, regulatory compliance, inflation, limited education and financial literacy, changing investment trends, and human resource competencies. To improve performance, DPLK must enhance its investment management quality by addressing these challenges and adopting strategies that optimize returns while managing risks.